Attitudes of Generation Y Nurses Toward Evidence‐Based Nursing Practice: A Mixed‐Methods Study - Juste Kiviliene; Aurelija Blazeviciene (Nursing Open)
ABSTRACT Aim To identify the attitudes of Generation Y nurses toward evidence‐based nursing practice in university and municipality level hospitals in Lithuania. Design A mixed‐methods study with a convergent parallel design was used, allowing simultaneous collection and analysis of quantitative and qualitative data. Methods The Evidence‐Based Practice Attitude Scale‐50 (EBPAS‐50) was employed in the quantitative phase, while focus group interviews were conducted in the qualitative phase. Of the 1955 surveys distributed, 1388 were fully completed (71% response rate), with Generation Y nurses (born 1980–2000) selected for further analysis (n = 368; 27.2%). Out of 14 invited nurses, eight participated in two focus group interviews. Results Generation Y nurses exhibited a positive attitude toward evidence‐based practice, valuing its relevance to patient needs and feedback. However, time constraints and administrative challenges were identified as key barriers. Qualitative analysis further revealed resources and organisational limitations in applying evidence‐based practice. Conclusion Generation Y nurses view evidence‐based practice positively and recognise its role in enhancing patient care. However, barriers like time constraints, administrative challenges, and limited resources hinder implementation. Critical thinking, teamwork, and organisational support are essential for successfully integrating evidence‐based practice into clinical practice. Implications for the Profession and/or Patient Care Generation Y nurses' attitudes toward evidence‐based practice, along with their perceptions of barriers and facilitators, can guide administration in developing strategies to enhance evidence‐based practice integration. Patient or Public Contribution Participants contributed to this study by agreeing to complete a questionnaire and answer questions during focus group interviews.